SCIENTIST WHO COMMENTED ON THE RUBAI OF BAHAUDDIN NAQSHBAND - Navruzova Gulchehra Nigmatovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article provides information about the life and spiritual heritage of the scientist Muhammad Sadiq Kusuri, the author of a book about the rubai of the founder of the teachings of Naqshbandiya Bahouddin Naqshband “Rubaiyoti Khoja Naqshband” and comments on 137 rubai’s in Urdu, which were so far not known to the general public.